Prevalence of malocclusion and orthodontic treatment need in 10-year-old New Zealand children - Johnson Mark; Harkness Michael (Sciendo, 2000)
The need for orthodontic treatment was determined in a random sample of 10-year-old Dunedin, New Zealand schoolchildren using the Dental Aesthetic Index (DAI); an index based on the social acceptability of dental appearance. When absent or unerupted teeth were disregarded, orthodontic treatment was considered to be "mandatory" for one-third of the children. The remaining children were almost equally divided into the three other treatment-need groups: "highly desirable", "elective", and "not necessary". The majority of the children had crowding and spacing in at least one incisor segment, and a molar occlusion other than Angle Class I. In this predominately mixed-dentition sample, more children were considered to need orthodontic treatment than older children in studies using the DAI. This raises some questions about the suitability of the DAI as a tool to assess orthodontic treatment need in mixed-dentition samples.